KONSTRUKSI SOSIAL DA'I SUMENEP ATAS PERJODOHAN DINI DI SUMENEP - Mohammad Rifai (Jurnal Dakwah Tabligh, 2020)
The early marriage is a classic discourse that has been pro-contra in the Madura people, both socially and culturally. Although, when referring to Islamic teachings, this early marriage does not violate the norms in Islamic teachings. The Madura people, especially Sumenep, views the early marriage as a culture that must be preserved. Because in Islam itself there is no Qur'anic argument or hadith that regulates the age of marriage. This reality seems to be a challenge for the da'i to answer the possibility of this early marriage.This study uses descriptive-qualitative research with the sociological approach of Peter L. Berger's social construction theory. The focus of this research is how the social construction of Sumenep over premature marriage.